The knowledge and perceptions of the risks of contracting HIV/AIDS and the sexual behavior of high school learners in Port St Johns Municipality, South Africa - Kibirige, Simon Namukonge (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.